Understanding New Yorkers' Everyday Life Information Seeking Behavior in the Context of Coping with COVID‐19. Issue 1 (13th October 2021) - Wu, Shuheng
Abstract: This poster presents preliminary findings of a study which examines New Yorkers' everyday life information seeking (ELIS) behavior in the context of coping with COVID‐19. Based on semi‐structured interviews with 10 New Yorkers, this study identified 15 major categories of everyday life information needs, and developed a typology of New Yorkers' preferred ELIS sources. These typologies show New Yorkers' specific ELIS behavior during the pandemic, such as actively seeking information regarding grocery shopping and delivery, health safety guidelines, and current events. Social media became a popular source for immediate, local, and relevant information in New Yorkers' daily lives. These findings could form a knowledge base to inform the development of information services to assist residents of large urban areas in coping with public health crises.